Fatal Methamphetamine Poisoning: Forensic Case Presentation (Iraqi Journal of Medical Sciences, 2025)
Background:    The rising number of methamphetamine abusers and the consequent fatalities prompted this case presentation, aiming to highlight the risks associated with its use and to enhance awareness of its detrimental effects on the human body.Case presentation:    The study examined a 30-year-old male who was discovered deceased at his home in the early morning. The autopsy showed no evidence of external or internal trauma and significant gross pathological alterations. A small torn nylon package was found in the stomach\'s lumen, its contents released. Toxicological tests of the stomach contents, blood, and urine identified methamphetamine in the package. Laboratory results indicated a lethal concentration. The liver tissue exhibited sinusoidal cholestasis, and the kidneys displayed severe acute renal tubular necrosis.Conclusion: The study highlights the toxic and irreversible impact of methamphetamine on different human organs and the lethal consequences of smuggling the substance through oral ingestion. Keywords: Amphetamine, methamphetamine, autopsy, tubular necrosis, sudden deathCitation: Sami SW, Al-Qazzaz MA. Fatal Methamphetamine Poisoning: Forensic Case Presentation. Iraqi JMS. 2025; 23(1): 25-31. doi: 10.22578/IJMS.23.1.3